2002
DOI: 10.1046/j.1524-4741.2002.08303.x
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Carcinoma In Situ of the Breast: A Comparative Analysis of Histology, Nuclear Area, Ploidy, and Neovascularization Provides Differentiation Between Low- and High-Grade Tumors

Abstract: Ductal carcinoma in situ (DCIS) is a heterogeneous group of lesions that has been subdivided into three types: well differentiated (grade I), moderately differentiated (grade II), and poorly differentiated (grade III). Forty-five cases of DCIS were analyzed for image analysis: nuclear area, DNA ploidy, and vascularization in order to establish a more precise correlation between the histologic grade and these morphometric parameters. Our results confirm that the mean nuclear area, DNA ploidy, and microvessel de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…In concordance with our study, Guidi et al found, using factor VIII-related antigen, significantly increased MD in IDC with comedonecrosis compared to those without comedonecrosis (33). Similarly, more recent studies supported the same conclusion (37)(38)(39).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In concordance with our study, Guidi et al found, using factor VIII-related antigen, significantly increased MD in IDC with comedonecrosis compared to those without comedonecrosis (33). Similarly, more recent studies supported the same conclusion (37)(38)(39).…”
Section: Discussionsupporting
confidence: 93%
“…Compared to IC, the studies for MD in IDC are relatively limited in the literature and have generally focused on blood vessel density (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Only two relatively recent studies (dedicated mainly to investigate lymphangiogenesis in breast cancer) commented on lymphatic vascular density in IDC of the breast in comparison with other breast lesions and without correlating it with the different prognostic parameters within the IDC (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding nuclear grading, there was a significant higher prevalence of edema in poorly differentiated carcinomas (G3) compared with well‐ and intermediate‐differentiated tumors (G1 and G2). Higher nuclear grading is associated with a more aggressive growth pattern, increased neoangiogenesis, and higher levels of proteolytic enzymes (23,28,31,32). According to the cited experimental literature and the statements above, a higher level of neoangiogenesis and proteolysis may be assumed in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate a lower MRI detection rate for DCIS compared to invasive ductal carcinoma. Pathologically it has been demonstrated that microvessel density differs with different grades of DCIS, with a higher microvessel density in the higher-grade lesions with comedo necrosis [59,60], and this is related to VEGF expression [61]. It would thus be reasonable to postulate that for low-grade DCIS, it is likely that absent contrast enhancement on MRI may be due to the lower angiogenetic activity.…”
Section: Non-enhancement Of Malignant Breast Lesionsmentioning
confidence: 99%